Peningkatan Hasil Belajar Mata Pelajaran PKn Materi Harga Diri Siswa melalui Media Video Motivasi di MIN Yogyakarta II - Karimatul Hissoh (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
Abstract This research aims to know the improvement of student learning outcomes towards an understanding of students 'self-esteem’ through motivational video media on subjects PKn. Social Problems in communities living around MIN Yogyakarta II cause a lot of negative impacts for students. In the Middle heterogennya the guardians of pupils with diverse jobs, legal violations/negative behaviour (theft bike ontel, free, cultural Association of gambling, and a brawl between groups) also occur. This very geographical location affects the input as well as the competitiveness of the students who enter the MIN Yogyakarta II. Therefore, the material